Qualifications of the professionals in the assessment for identification of intelectual disability in the school - Veltrone, Aline Aparecida (2011)
This paper aimed to describe qualifications of education professionals in the assessment for identification of intellectual disability as well as the procedures used in this process. A total of 67 professionals of special schools, and mainstream municipal and state schools of five towns within the State of São Paulo participated in the study. The data were gathered and used to describe in detail the evaluation team formation, including their position, academic background, and the methods used in the assessment. In general, the data show that there are no standards of competence for professionals involved in the assessment including the lack of established methodological and procedural guidelines for such evaluations. Moreover it also indicates that different methodologies have been employed by special school and within the municipal and state education system. Furthermore, the study points out that intellectual disability is ultimately understood in terms of both the demand for support for pupil with intellectual impairment and the concepts of the immediate social and cultural context in which the learning occurs and where the student takes part in a range of activities.